Comparative analysis of antigen and molecular tests for the detection of Sars-CoV-2 and related variants: A study on 4266 samples. (July 2021) - Caputo, Valerio; Bax, Cristina; Colantoni, Luca; Peconi, Cristina; Termine, Andrea; Fabrizio, Carlo; Calvino, Giulia; Luzzi, Laura; Panunzi, Giorgia Gaia; Fusco, Claudia; Strafella, Claudia; Cascella, Raffaella; et al.
Highlights: Antigen test revealed high accuracy in 4266 samples from naso-oropharyngeal swabs. Antigen test identified positive samples with high viral load by high pg/mL levels. Reduced concordance was shown as viral load decreases. Antigen testing identified variant carriers according to their viral load. Antigen test may be suitable as a first-line screening in low prevalence areas. Abstract: Objectives: The present study compared the performance of the Lumipulse G Sars-CoV-2 Ag kit with the TaqPath COVID-19 RT-PCR CE IVD kit. Methods: The study was conducted on 4266 naso-oropharyngeal swabs. Samples were subjected to antigen RT-PCR tests for the detection of Sars-CoV-2 and related variants. Statistical analyses were conducted in R software. Results: We found 503 positives (including 138 H69-V70 deletion carriers) and 3763 negatives by RT-PCR, whereas 538 positives and 3728 negatives were obtained by antigen testing. We achieved empirical and binormal AU-ROCs of 0.920 and 0.990, accuracy of 0.960, sensitivity of 0.866, specificity of 0.973, positive and negative predictive values of 0.810 and 0.980. We obtained a positive correlation between viral loads and antigen levels (R 2 = 0.81), finding a complete concordance for high viral loads (log 10 copies/mL > 5.4). Antigen levels > 222 pg/mL were found to be reliable in assigning positive samples ( p < 0.01). Concerning variant carriers, antigen test detected them with the same accuracy as other positive samples. Conclusions: Molecular and antigen tests should be evaluated regarding the prevalence of the area. In case of low prevalence, antigen testing can be employed as a first-line screening for the timely identification of affected individuals with high viral load, also if carriers of Sars-CoV-2 variants.